Deskripsi dan Potensi Wisata Tirta Sari Songsang Kabupaten Agama - Helmi, Dewilna (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2022)
Tirta Sari Songsang Tourism is a concept introduced in the Agam Regency, West Sumatra. This research study is described in the form of a general overview of tourism and a specific analysis of the tourism potential of Tirta Sari Songsang. The data in this study were collected through a descriptive qualitative approach, using interviews, observations, field surveys, and documentation of Tirta Sari Songsang tourism. Based on the analysis, the Songsang tourism site is located on the outskirts of the hills, about 30 minutes from the centre of Bukittinggi. Tirta Sari Songsang offers visitors natural tourism experiences with supporting facilities such as a prayer room (mushola), toilets, and attractions typical of nature-based tourism. However, some areas for improvement were identified, such as access to the tourist site, which remains suboptimal, with potholes found in several sections of the road leading to the location. Additionally, facilities such as toilets need to be fully functional due to inadequate maintenance and upkeep, preventing these amenities from being utilized to their full potential.